Reseña evolutiva de la especialidad de Periodontología en la provincia Las Tunas - Fontaine-Machado, Omelio; López-Reyes, Odalmis; Figueredo-Pérez, María Caridad; Figueras-González, Belissa; Frometa-Dominguez, Danai; Suàrez- Gonzàlez, Mayelin De la Caridad (Revista Electrónica Dr. Zoilo E. Marinello Vidaurreta, 2025)
Research of a historical nature with the purpose of briefly exposing the development of Periodontology in the province of Las Tunas. This specialty has been increasing gradually and today has fully competent professionals to offer quality specialized dental care; by linking to the teaching-care activity, with a faculty of five well-qualified pedagogues. It can be stated that the formation of human capital has increased in these years that the specialty has passed according to the requirements and needs of the population and the National Health System. The improvement and preparation of already trained doctors and new specialists has also been encouraged to safeguard the periodontal health of the population.